Digitization of Cultural Heritage and Related Issues of Intellectual Property - Mohanty, Sasmita; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Cultural heritage has an unquestionable role to play in shaping national identity, sustainable development and the competitiveness of creative industries. In light of the new emerging possibilities in protecting, maintaining and popularizing cultural heritage, the issues surrounding intellectual property posed serious challenges. Such criteria call for broad cultural policy strategic planning, including the preservation of intellectual possession of cultural heritage; digitalization as a medium of economic use and appreciation of it as a market tool for creative industries. The study examined the economic symbiosis between intellectual property and cultural heritage, exposed cultural values in their economic context and showed that intellectual property is adequate for security and provided a step by step framework for intelligent control of digitized cultural values. The main thesis is the need for a clear balance between national economic and cultural policies in terms to intellectual property rights to create an economic symbiosis of cultural heritage and creative industries.